NU Online as a Space for the Production of Contemporary Religious Knowledge: A Study of Literacy, Education, and Harmony Among Ummah Based on Digital Media - Imam Hidayat; Hamid Samiaji, Mukhamad; Hafidz, Nur (Jurnal Nusantara Raya, 2025)
The development of digital technology has changed the way people access and produce religious knowledge. In the midst of a fast and complex flow of information, NU Online is present as a digital media platform that represents the moderate Islamic tradition based on Ahlussunnah wal Jamaah. This research aims to analyze how NU Online plays a role as a space for the production of contemporary religious knowledge through three main focuses: religious literacy, Islamic education (formal and non-formal), and the promotion of harmony between religious communities. This study uses a descriptive qualitative approach with a content analysis method for NU Online articles published in the 2020–2024 period. The data were analyzed thematically to identify the representation of values, religious discourse, and communication strategies used. The results of the study show that NU Online not only functions as a medium for disseminating information, but also as a cultural institution that maintains the heritage of traditional Islamic literacy, strengthens pesantren education in digital format, and mainstreams the narrative of tolerance and inclusivity between religions. These findings show that digital media based on Islamic organizations has strategic potential in preserving, modernizing, and democratizing religious knowledge. The implication is that NU Online can be used as a model for the development of moderate religious media in the digital era that is full of disruption.